Using the SPT value to compare with theoretical methods for calculating the ultimate Bearing capacity of shallow foundations - Abir. A. Elazzabi (مجلة البيان العلمية, 2023)
Estimation of the ultimate bearinga capacity of the soil supporting foundation is one of the important requirements to develop safe design of foundations. There are many methods used to estimate bearing capacity of soil such as theoretical, empirical and field tests. There are different methods proposed to estimate the theoretical ultimate bearing capacity. In this work, we will carry out to compare the obtained results using theoretical equations with the results of standard penetration test (field Test). To achieve the goal of study, Terzaghi (1943), Meyerhof (1963), Hansen (1970), Vesic (1973) was chosen. Results SPT for 10 sites from the geotechnical report collected from projects to construct communication towers in the cities of Sirte, Misurata, Gharyan, Tarhuna and Tripoli. Were used to conduct this analysis. the calculations showed that the obtained results, they were found that the values from the Ultimate Bearing capacity calculated using standard penetration test are far from the theoretical methods and it is not possible to compare them. Geotechnical investigation of the subsoil strata from several sites are based on the data collected from trial pits and from laboratory results. The conclusion presented in this paper is limited to allowable bearing capacity in these sites to these soils. However, it can be for any soils.